Image analysis in Gomori´s trichrome stain of skeletal muscles subjected to ischemia and reperfusion injury (2016)
Conditions that produce ischemia and reperfusion injury include orthopedic surgeries, vascular diseases and accidents in remote places in which use of a manual tourniquet is required. Tissues under such stress suffer the consequences of evidenced by changes in their normal microscopic organization that can be reversible or irreversible according to the time and severity of lesion. An experimental model of ischemia has been designed taking into account the characteristics similar to a surgical procedure, from preparation for anesthesia up to the postsurgical follow up of each animal until it finishes the established time of reperfusion. Two muscles, soleus and extensor carpi radialis longus, dissected from Wistar rats that were underwent to short periods of ischemia and short and prolonged periods of reperfusion up to 32 days. There were no significant changes in the macroscopic weight of muscles, but significant differences were found in the area occupied by intramuscular extracellular matrix. During reperfusion, a partial recovery was observed until the last day of study. If we pretend to extrapolate these results to clinical areas, its importance focuses in the recovering of function and the following up of patients after surgical procedures as studied in the present experiment.